Eye Motility Alterations in Retinitis Pigmentosa - Raffaele Migliorini; Anna Maria Comberiati; Giovanni Galeoto; Manuela Fratipietro; Loredana Arrico (Journal of Ophthalmology)
Purpose. We evaluated a sample of individuals with retinitis pigmentosa (RP) with the aim of assessing the presence or absence of ocular motility (OM) disorders. Materials and Methods. We included 23 out of the 25 individuals from the sample (9 females and 14 males) with an average visual acuity of 6/10. Results. The cover test about the vertical deviation in near distance showed an r/l in 3.45% and an l/r in 6.9%. The assessment of OM showed that 39.1% of the sample had a severe hyperfunction of the IO of the right eye and a severe hyperfunction (34.5%) of the SO of the left eye; 21.8% had a moderate hypofunction of right SO with a moderate percentage of hypofunction of 17.5% for the SO of the left eye; 30.5%, however, showed a serious hypofunction of the SR of both eyes; 21.7% of the sample showed a hyperfunction in both eyes of the IR. Conclusion. This alteration, however, is not attributable to either a high refractive defect (medium-low myopia: −1 diopter ±3 SD) or to a severely impaired binocular vision (visual acuity, motor fusion, and stereopsis are normal or within a range of values commonly accepted). Therefore, the disorders of OM lead to a genetic origin.